PENINGKATAN MINAT BACA SISWA MELALUI PENGEMBANGAN PERPUSTAKAAN BERBASIS DIGITAL - Asadi, Ahmad Ahya; Dharmayanti, Agustin Wulan Suci (LP2M Universitas Jember, 2024)
Education is essential for every individual, as everyone has the right to grow through learning. Education is fostered by promoting a culture of reading, writing, and numeracy for all members of society. Despite achieving a 99.1% literacy rate, Indonesia still struggles with a low reading culture. It appears that literacy skills do not necessarily correlate with people's interest in reading. To address this, a literacy program aimed at boosting students' reading interest through the development of a digital library was implemented at MTs Bustanul Ulum in Locare Village. The KKN Back To Village III program, which took place from August 11 to September 9, 2021, focused on the theme of